2011
DOI: 10.1007/s00792-011-0400-5
|View full text |Cite
|
Sign up to set email alerts
|

Rhamnolipid-producing thermophilic bacteria of species Thermus and Meiothermus

Abstract: Novel rhamnolipid-producing strains of three thermophilic bacteria, Thermus sp., T. aquaticus and Meiothermus ruber were identified that have not been previously described as rhamnolipid producers. Rhamnolipids were extracted from supernatant and further purified by thin-layer chromatography. Mass spectrometry with negative electrospray ionization revealed 77 rhamnolipid homologues varying in chain length and unsaturation. Tandem mass spectrometry identified mono-rhamnolipid and di-rhamnolipid homologues conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 32 publications
1
20
0
2
Order By: Relevance
“…chlororaphis NRRL B-30761 is the first reported wildtype nonpathogenic organism that solely produces R 1 L (Gunther et al 2005(Gunther et al , 2007. Other reported RL-producing wild-type bacteria, including the non-Pseudomonas species (Hošková et al 2013;Řezanka et al 2011;Tavares et al 2013), synthesize a mixture of R 1 L and R 2 L. Therefore, in the present study, we genetically engineer the nonpathogenic NRRL B-30761 into an R 2 L-producing strain by expressing a heterologous rhlC gene in the organism. The resultant recombinant, P. chlororahis [pBS29-P2-rhlC], was shown to produce R 2 L at a level that is 2.4 times higher than R 1 L ( Table 2).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…chlororaphis NRRL B-30761 is the first reported wildtype nonpathogenic organism that solely produces R 1 L (Gunther et al 2005(Gunther et al , 2007. Other reported RL-producing wild-type bacteria, including the non-Pseudomonas species (Hošková et al 2013;Řezanka et al 2011;Tavares et al 2013), synthesize a mixture of R 1 L and R 2 L. Therefore, in the present study, we genetically engineer the nonpathogenic NRRL B-30761 into an R 2 L-producing strain by expressing a heterologous rhlC gene in the organism. The resultant recombinant, P. chlororahis [pBS29-P2-rhlC], was shown to produce R 2 L at a level that is 2.4 times higher than R 1 L ( Table 2).…”
Section: Discussionmentioning
confidence: 96%
“…Rhamnolipids (RLs) are a family of rhamnose-containing glycolipids first characterized in Pseudomonas aeruginosa (Jarvis and Johnson 1949) and had since been described in other bacteria (Gunther et al 2005(Gunther et al , 2007Řezanka et al 2011;Tavares et al 2013;Toribio et al 2010). The lipid portion of most RLs consists of 3-hydroxyalkanoyl-3-hydroxyalkanoate (C x -C y , where x and y are the carbon chain lengths of the alkanoate) moiety, though some may contain only a monomeric 3-hydroxyalkanoate.…”
Section: Introductionmentioning
confidence: 99%
“…Yet one more example is the thermophilic bacterium Thermus thermophilus HB8, which also produces RLs (TthRLs) in large amounts using sunflower seed oil, sodium gluconate or glucose as carbon source [10,11]. Bacteria Thermus sp., Thermus aquaticus and Meiothermus ruber produce RLs varying in chain lengths up to unusually long chains with 24 carbon atoms and unsaturation [12].…”
Section: Introductionmentioning
confidence: 99%
“…Rezanka et al (2011) reported new RL-producing extremophilic strains such as the thermophilic bacteria, Thermus sp., T. aquaticus and Meiothermus ruber. RL derivatives were characterized as mono-rhamnolipid and di-rhamnolipid homologues containing one or two 3-hydroxy-fatty acids, saturated, monounsaturated or diunsaturated, even-or odd-chain, up to unusual long chains with 24 carbon atoms (Rezanka et al, 2011). Exploring the marine environment would yield novel halotolerant biosurfactants, but reports from the marine environment are limited.…”
Section: Marine Microbes As Potential Source Of Rl Biosurfactantsmentioning
confidence: 99%